Gendered lives, gendered Vulnerabilities: An intersectional gender analysis of exposure to and treatment of schistosomiasis in Pakwach district, Uganda. - Sarah N Ssali; Rosemary Morgan; Salama Nakiranda; Christopher K Opio; Mariam Otmani Del Barrio (PLoS Neglected Tropical Diseases)
Introduction Schistosomiasis is a neglected tropical disease (NTD) that is endemic in Uganda, despite several interventions to eliminate it. It is transmitted when people infected with it pass on their waste matter into fresh water bodies used by others, consequently infecting them. Several studies have demonstrated gender and age differences in prevalence of schistosomiasis and NTDs such as lymphatic filariasis and soil transmitted helminths. However, few intersectional gender analysis studies of schistosomiasis have been undertaken. Using the World Health Organisation (WHO)'s intersectional gender analysis toolkit, this study was undertaken to identify which social stratifiers most intersected with gender to influence vulnerability to and access to treatment for schistosomiasis disease, to understand how best to implement interventions against it. Methodology This was a qualitative study comprising eight focus group discussions (FGDs) of community members, disaggregated by age, sex and location, and 10 key informant interviews with health care providers and community leaders. The Key informants were selected purposively while the community members were selected using stratified random sampling (to cater for age, sex and location). The data was analysed manually to identity key themes around gender, guided by a gender and intersectionality lens. Results The study established that while the River Nile provided livelihoods it also exposed the community to schistosomiasis infection. Gender relations played a significant role in exposure to and access to treatment for schistosomiasis. Traditional gender roles determined the activities men and women performed in the private and public spheres, which in turn determined their exposure to schistosomiasis and treatment seeking behaviour. Gender relations also affected access to treatment and decision making over family health care. Men and some women who worked outside the home were reported to prioritise their income earning activities over seeking health care, while women who visited the health facilities more regularly for antenatal care and to take sick children were reported to have higher chance of being tested and treated in time, although this was undermined by the irregular and infrequent provision of praziquantel (PZQ) mass drug administration. These gender relations were further compounded by underdevelopment and limited economic opportunities, insufficient health care services, as well as the respondent's age and location. Conclusions The study concludes that vulnerability to schistosomiasis disease and treatment occurred within a complex web of gender relations, culture, poverty, limited economic opportunities and insufficient health services delivery, which together undermined efforts to eliminate schistosomiasis. This study recommends the following: a) increased public health campaigns around schistosomiasis prevention and treatment; b) more regular PZQ MDA at home and schools; c) improved health services delivery and integration of services to include vector control; d) prioritising NTDs; e) providing alternative economic activities; and f) addressing negative gender norms that promote social behaviours which negatively influence vulnerability, treatment seeking and decision making for health.